Effect of fluorine doping on the NO2-sensing properties of ZnO thin films - Sennik, Erdem; Kerli, Suleyman; Alver, Umit; Ozturk, Zafer Ziya (Elsevier Science Sa, 2015)
Fluorine-doped ZnO (FZO) thin films were fabricated on glass substrates using a chemical spray pyrolysis method for NO2 gas detection. The physical properties of the films were investigated by X-ray diffraction (XRD), scanning electron microscopy (SEM) and ultraviolet-visible (UV-Vis) spectrometry as a function of fluorine concentration (2 and 5 at%). The films exhibited a hexagonal wurtzite structure, and the inclusion of fluorine did not significantly influence the morphology of the films. Optical measurements showed that the band gap energies of the films were affected by the fluorine concentration. Furthermore, the NO2 gas-sensing properties of pristine and FZO thin films were investigated in the concentration range of 100-1000 ppb. Fluorine doping in ZnO was found to improve the NO2-sensing capability at the least. All gas sensor measurements showed an optimal sensor response at a temperature of 200 degrees C. In addition, the 2% FZO was found to be more suitable candidate for detecting NO2 gas. (C) 2015 Elsevier B.V. All rights reserved.
Keywords: Metal oxide; ZnO; Spray method; F dopant; Gas Sensor; NO2